THE ACCOUNTING EXCHANGE. - Littleton, A. C. (The Accounting Review, 1946)
Abstract The Smaller Practitioner; This thinking gives support to George O. May's statement that "Accounting has developed from a service department of business to become a social force." It also suggests that public accountants are aware they must accept new obligations to society as their technology becomes a social force. They have clearly accepted the duty to get qualified people into the profession. The support given to university education in the subject and to the work of providing suitable technical examinations and of fostering effective legislation is a part of this activity. So too, is the stress now placed upon selective recruiting and the development of a program of personnel testing. It is also a social obligation, as well as sound firm policy, to aid staff people to attain full competence. To this end some firms provide special training for beginners and diversify the experience as an aid to their professional growth. These small firms, located for the most part in the smaller business communities, would often prove to be missionaries for good accounting in business.